Apparent Induction of Xylanase by Bacillus pumilus PU4-2 using Pretreated Substrates - SHERLY WIDJAJA; TRESNAWATI PURWADARIA; PIUS PERTUMPUN KETAREN (Microbiology Indonesia, 2008)
Bacillus pumilus PU4-2 produces xylanase (â-1,4-D-xylan xylanohydrolase; EC 3.2.1.8) in wheat pollard with high activity. Water and NaOH-soaked pollard were used in this research to enhance the production of assayable enzyme. Enzyme activity was produced in minimal media containing 3% w/v untreated or water or NaOH-soaked pollards in 250 ml flasks incubated on shaker incubator at 30°C and 150 rpm for 36 h. The production was also compared to untreated oatmeal known as an inducer substrate. The highest xylanase activity was obtained by using untreated pollard as a sole carbon source. The enzyme activity was 157 U ml-1 with specific activity at 718 U mg-1. Xylanase production using different soaking time for water pretreated pollard also confirmed that untreated pollard was the best inducer. The production was not influenced by different water soaking times used to remove reducing sugar. Although pretreatment decreased the reducing sugar, the reduction did not enhance assayable enzyme levels. The production was best induced by the soluble oligosaccharides of untreated pollard. We conclude that B. pumilus PU4-2 was able to produce xylanase with reducing sugar content up to 660 ppm present in production medium. With this reducing sugar level, repression of enzyme production was not detected in the production medium.